Ramps & pathways a constructivist approach to physics with young children - DeVries, Rheta; Sales, Christina; National Association for the Education of Young Children (Washington, D.C. National Association for the Education of Young Children, 2011)
Provides an introduction to constructivist physics with classroom examples illustrating how children construct knowledge. Shows how to promote children's scientific reasoning by engaging them in active experimentation.
Can I have your shovel? -- Ramps materials -- Thinking about children's thinking (or, why we take a "constructivist" approach) -- Doing constructivist physical science -- Mental relationships children can construct -- Ten principles of teaching : working with children in Ramps & Pathways activities -- The story of Nani (or, a case where Ramps & Pathways made a difference).
Keywords: Physics -- Study and teaching (Early childhood); Physics -- Study and teaching (Primary); Early childhood education -- United States; Constructivism (Education)